(untitled) (Perner’s Contacts, 2023)
The pharmaceutical industry’s profitability has attracted attention, but it faces challenges from counterfeiters exploiting vulnerabilities worsened by globalization and complex supply chains. In 2019, European authorities introduced regulation EU 2016/161 to enhance drug supply chain security and traceability. By conducting a systematic literature review, this study assesses the effectiveness of the European Drug Serialization system, examining its implementation and the potential benefits of integrating digital technologies like RFID and Blockchain. The aim is to investigate and identify measures contributing to the strengthening of pharmaceutical supply chains against counterfeiting. The research suggests that while serialization is crucial, it may not provide foolproof security, emphasizing the need for additional digital technology integration.